Gender Intervention Through Toxic Masculinity in Hashimi's The Pearl That Broke Its Shell - Anik Cahyaning Rahayu; Ali Romadani; Sudarwati Sudarwati (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2022)
This article is about the idea of gender intervention through toxic masculinity reflected in Nadia Hashimi’s The Pearl That Broke Its Shell based on the theory of toxic masculinity by Terry A. Kupers. Beginning from a position that sees masculinity as a socially constructed idea in a patriarchal culture, this article works through the concept that hegemonic masculinity under patriarchy can turn toxic. There is a connection between toxic masculinity and hegemonic masculinity because toxic masculinity deviates from hegemonic masculinity aspects that are destructive. Many toxic masculinity traits can be found in society. This research uses a descriptive qualitative research design since this study will be limited to explain on two traits that are found in the novel. The most prominent traits that can be found in the novel are the subordination of women and violence. The idea of subordination of women can harm women because it puts them in an inferior position. This idea is also harmful to men as well when they could not meet society’s expectation of being “real” men. Toxic masculinity also has the belief that to prove their manhood, men have to be able to act violently. From that idea, some characters in the novel perform violence because they want to fit society’s expectation of being a “real” man. This study concludes that the hegemony of masculinity under a patriarchal society can result in a bad situation where men are viewed as superior and women as inferior. It can push the idea of toxic masculinity, which is harmful to both men and women. It is because men's superior position in this situation can be destructive and harmful for both men and women.